2009
DOI: 10.1073/pnas.0900655106
|View full text |Cite
|
Sign up to set email alerts
|

TNF/iNOS-producing dendritic cells are the necessary evil of lethal influenza virus infection

Abstract: Respiratory infection with highly pathogenic influenza A viruses is characterized by the exuberant production of cytokines and chemokines and the enhanced recruitment of innate inflammatory cells. Here, we show that challenging mice with virulent influenza A viruses, including currently circulating H5N1 strains, causes the increased selective accumulation of a particular dendritic cell subset, the tipDCs, in the pneumonic airways. These tipDCs are required for the further proliferation of influenza-specific CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
421
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 379 publications
(448 citation statements)
references
References 29 publications
20
421
2
5
Order By: Relevance
“…Since they also expressed CD83 (Fig. 3C), TNF-a and iNOS, they could resemble Tip-DCs previously described in mice [3][4][5] and humans [22]. …”
supporting
confidence: 70%
See 2 more Smart Citations
“…Since they also expressed CD83 (Fig. 3C), TNF-a and iNOS, they could resemble Tip-DCs previously described in mice [3][4][5] and humans [22]. …”
supporting
confidence: 70%
“…While DCs display a dendritic form and exhibit DC functions during steady state, inflammatory DCs, derived from CCR2 1 monocytes, only appear as a consequence of infection or inflammation [2]. Recent studies in mice have identified a subset of inflammatory DCs, known as TNF/iNOS-producing DCs (Tip-DCs), that are important for the clearance of Listeria monocytogenes bacteria [3]; influenza virus [4]; and regulation of IgA production in mucosal immunity [5]. Since the differentiation of monocytes into DCs or macrophages relies on the microenvironment, the presence of different T-cell types and cytokines is a critical feature in determining the differentiation outcome [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overexpression of these cytokines causes a variety of complications and pathological injuries. Previous studies reported that TNF‐α and IL‐6 could aggravate the clinical symptoms and histopathological changes of influenza virus‐infected mice 41, 42. We hypothesize that SCG could stabilize the membrane of mast cells, which inhibits the release of inflammatory mediators and alleviates the inflammatory response induced by H5N1 infection.…”
Section: Discussionmentioning
confidence: 78%
“…Functionally, moDCs are major producers of pro-inflammatory cytokines (Serbina et al, 2003;Xu et al, 2007;Zhan et al, 2010), inducers of Th1 differentiation (Leon et al, 2007) and memory T cell activation (Wakim et al, 2008), and antigen cross-presenting cells (Cheong et al, 2010). By exhibiting these potent functions, moDCs offer a protective immunity role as well as mediate immunopathology (Aldridge et al, 2009). In autoimmune inflammation, moDCs are likely to be the major mediators of pathology (Campbell et al, 2011).…”
Section: Monocyte-derived Dendritic Cells (Modcs) Become a Major DC Smentioning
confidence: 99%